1995
DOI: 10.3406/amime.1995.1279
|View full text |Cite
|
Sign up to set email alerts
|

Aiguisoirs, polissoirs médiévaux en os (Xle-XIVe s.) dans le sud-ouest de la France

Abstract: Inventaire, description et analyse d'une centaine de pièces taillées dans des mandibules, radius, métapodes et tibia de bœuf, de cheval ou d'âne, et portant des séries plus ou moins régulières de ponctuations. Ces dernières ont été faites à l'aide d'un outil pointu qui, lors de sa percussion sur l'os, soulevait une petite écaille de matière, rendant la surface râpeuse. Elles ont été interprétées comme des aiguisoirs/polissoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…For a long time, the ultimate function of a number of artifacts made of bone with a set of asymmetric rows of triangular indentations was an enigma that generated various explanations in the archaeological literature (Semenov 1964; Briois et al 1995; Benco et al 2002; Rodet-Belarbi et al 2002). In the early 21st century, some ethnographic studies demonstrated that blacksmiths used these worked bones as an anvil to anchor the metal blade of a sickle while it was being cut to make a serrated edge (Aguirre et al 2004; Esteban and Carbonell 2004).…”
Section: Introductionmentioning
confidence: 99%
“…For a long time, the ultimate function of a number of artifacts made of bone with a set of asymmetric rows of triangular indentations was an enigma that generated various explanations in the archaeological literature (Semenov 1964; Briois et al 1995; Benco et al 2002; Rodet-Belarbi et al 2002). In the early 21st century, some ethnographic studies demonstrated that blacksmiths used these worked bones as an anvil to anchor the metal blade of a sickle while it was being cut to make a serrated edge (Aguirre et al 2004; Esteban and Carbonell 2004).…”
Section: Introductionmentioning
confidence: 99%